Alasan Individu Melajang: Sebuah Studi Literatur - Annisa, Romadoni Kun; Azmi, Belladiena; Chusairi, Achmad (Buletin Riset Psikologi dan Kesehatan Mental, 2025)
Staying single (unmarried) become common option in today worlds. Being single is a complex phenomenon influenced by many factors. This study conducts a systematic literature review (SLR) method to identify the determinants of decision for staying single. A comprehensive search was conducted among four databases, such as ScienceDirect, JStor, SAGE, and Scopus for articles published between 2012 and 2022 using keywords “singlehood” OR “singleness” OR “celibacy” AND “reasons” OR “determinants”. The systematic literature review identifies five major themes: sociodemographic factors, beliefs in marriage and romantic relationships, career orientation, traits and personality, and biological factors.